From door to diagnosis: A case report of a rare and life-threatening presentation of Takayasu arteritis - Eiad Habib; Laura MacPhee; Fawad Aslam; Bhavesh Patel; Ayan Sen; Lisa LeMond; Ina Soh; Chelsea Marshall; Marie Grill; Kartik Mangipudi; Nolan McBride; Hiroshi Sekiguchi (SAGE Open Medical Case Reports)
Takayasu arteritis is a chronic, large vessel vasculitis that typically affects the aorta and its main branches. We present a case of a 33-year-old male patient who was diagnosed with Takayasu arteritis after being admitted for acute cardiogenic shock requiring inotropes. Initial transthoracic echocardiography demonstrated severe biventricular dysfunction. Computed tomography imaging of his chest showed pulmonary infarcts. Patient subsequently developed sudden lower extremity weakness and bowel incontinence, and urgent magnetic resonance imaging of his spine demonstrated thoracolumbar vascular myelopathy. Transesophageal echocardiography revealed diffuse symmetrical thickening of the walls of the aorta; findings suggestive of aortitis. Patient was initiated on intravenous corticosteroid and systemic anticoagulation. Subsequent computed tomography angiography demonstrated irregular luminal contour of the aortic arch, and complete occlusion of the left subclavian artery, abdominal aorta, superior mesenteric artery, and left renal artery. He underwent an emergent aortoiliac thrombectomy. He was transitioned to oral prednisone, tocilizumab, and azathioprine with excellent recovery.